Conhecimentos, atitudes e práticas de profissionais de enfermagem sobre tuberculose pulmonar em um hospital escola de Fortaleza - Lopes, Fagner Liberato (2023)
Pulmonary Tuberculosis (TB) is a preventable, treatable and curable disease, but it is still considered a public health problem. It has been a priority for public health policies for almost 40 years, both nationally and internationally. In 2022, in Brazil, the incidence rate was 36.3 cases per 100 thousand inhabitants, cure reached 66.5%, abandonment was 14% and deaths were 2.38 per 100 thousand inhabitants. The general objective of this work is to analyze knowledge, attitudes and practices of nursing professionals at a hospital institution about Pulmonary TB. This is a cross-sectional, descriptive study, with a quantitative approach, of the Knowledge, Attitudes and Practices type. The research setting was the Walter Cantídio University Hospital and the participants were nursing professionals from the three categories (nurses, nursing technicians and nursing assistants) who work at that hospital. We used a questionnaire following the methodology for developing the CAP Survey and statistical analysis in data processing. As results of the research, we have: the majority of respondents were female, mixed race and with a specialist title. The majority's age range was between 41 and 59 years old and 62.7% of them considered themselves well-informed about pulmonary TB. When comparing the responses of higher and secondary level professionals, we noticed that the former had a better level of knowledge, except for identifying the four classic signs of pulmonary TB. While 32.1% of nurses identified these signs, 54.5% of mid-level professionals made this identification. When we compared the knowledge variable to professional categories, we noticed that nursing technicians had a lower average score than nurses and nursing assistants, presenting a statistically significant difference. We conclude that nursing professionals have satisfactory knowledge, but there are gaps in knowledge regarding basic aspects regarding the diagnosis, classic signs, cure and prevention of pulmonary TB.